Efektivitas Model CTL Terhadap Kemampuan Pemecahan Masalah Matematis: Studi Eksperimen Pada Siswa Sekolah Dasar - Putri, Hefna Alkhila Saira; Nasikhah, Putri Maftukhatun; Anastasia, Resti; Amaliyah, Fitriyah (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematical problem-solving ability is a critical 21st-century competency that needs to be developed from the early stages of education. However, field observations indicate that many elementary school students still struggle with solving problems related to fraction operations, especially when the problems are presented in contextual forms that require flexible application. This study aims to examine the effectiveness of the Contextual Teaching and Learning (CTL) model in improving the mathematical problem-solving skills of fifth-grade students at SDN 6 Cendono Kudus. The method used is quantitative with a quasi-experimental design and a Nonequivalent Control Group Design approach. The instruments employed were pre-test and post-test assessments covering problem-solving indicators based on Polya’s steps. The analysis results show a significant increase in post-test scores in the class using the CTL model, with a significance value of 0.028 (< 0.05) and an average N-Gain score of 0.3880 (moderate category). These findings indicate that the CTL model is effective in enhancing students’ mathematical problem-solving abilities, particularly because this approach links the material to real-life contexts, making learning more meaningful and relevant. This study recommends the implementation of CTL as an alternative instructional model that fosters active student engagement and conceptual understanding in elementary school mathematics.